36 One Year Follow-ups On Vascularisation At The Proximal Plantar Fascia In Patients With Chronic Plantar Fasciitis. (5th September 2014) - Fu, Siu Ngor; Chen, Holly HY
Abstract : Introduction: In patients with tendinopathy/fasciopathy, increase in vascularisation is observed in some but not all patients. However, decrease in vascularity has been observed in those successfully treated patients. A question therefore arises as whether the changes in vascularity would be difference in patients with and without vascularisation. The objective of the present study was to delineate the temporal changes in vascularisation in patients with chronic plantar fasciitis after a course of extracorporeal shock wave therapy. Methods: Thirteen eight patients with chronic plantar fasciitis (age: 47.0 ± 7.4years, BMI: 25.8 ± 3.8, duration of symptom : 3 to 36 months) participated in this study. Doppler signals were obtained in Power Doppler mode using an Esaote MyLab 70 X-view ultrasound unit with a 4–13 MHz linear transducer (Esaote, Genova, Italy) at the proximal portion of the plantar fascia at 5 time points. These include pre-, post-, 3-months, 6 months and 1 year after 6-session of extracorporeal shock wave therapy, at the treated and untreated heels. Vascularity index (VI) was computed off-line using a self-written software progam (Matlab, version 7.3.0.267R2006b). Range of interest (ROI) was drawn manually along the boundary of the proximal plantar fascia within a colour box of 1.5 * 1 cm in each image. VI was calculated as the ratio of the number of colour pixels to the total number of pixels within the ROI. Patients were categorised into vascularized and non-vascularized groups based on pre-intervention vascularisation. Results: In patients with chronic plantar fasciitis, the painful heel had higher VI (2.6%) than the non-painful heel (1.5%; p = 0.000). 15 (39.5%) patents were classified as vascularized group (with VI >2.6%). VI slight increase than decrease after a course of ESWT and reached a significant level at 6-month post intervention. However, in the non-vascularized patients, significant increase in VI was observed immediately after ESWT but returned to the pre-intervention level at 3-months post intervention. In the vascularized patients, reduction of VI was observed after ESWT and the reduction reached a significant level at 6-month and maintained at 1 year post intervention (Figure 1 ). Discussion: Changes in vascularisation were observed in patients with chronic plantar fasciitis after 6-session of ESWT at the treated but not the untreated heel. The changes in vascularisation depend on the pre-intervention vascularity. An initial increase in vascularisation was observed in the non-vascularized group but a continued decline in vascularisation was noted in the vascularized group. At 1-year post intervention, the vascularisation is similar to the non-painful heel.